Dylematy dotyczące podwyższania wieku emerytalnego - Klimkiewicz, Aldona (Dilemmas of Raising the Retirement Age, 2008)
Population ageing is one of the most important challenges facing the retirement systems of many countries. It would place substantial pressures on public finances. The negative consequences of ageing could be offset by rising the retirement age. But there are numerous work disincentives and employment barriers facing older workers which often result in early exit from the labour market. The best form of employment protection for older workers is to improve their employability and increase the range of job opportunities. Employers play a crucial role in shaping the employment prospects of older workers. To counter negative employer attitudes age-discrimination legislation and the information campaign should be introduced.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 157-165